Edible films based on chia flour: Development and characterization. Issue 2 (29th June 2015) - Dick, Melina; Henrique Pagno, Carlos; Haas Costa, Tania Maria; Gomaa, Ahmed; Subirade, Muriel; de Oliveira Rios, Alessandro; Hickmann Flôres, Simone; Lagarón, José M.; López‐Rubio, Amparo; Fabra, María José
ABSTRACT The aim of this study was to develop and evaluate the structural, physicochemical, barrier (water vapor), and mechanical properties of chia flour (CF)‐based films. The films were prepared with the casting method. Three ratios of CF to maize starch (MS), namely, 1:0, 1:1, and 1:2 w/w, were evaluated. A fixed total solid content of 6% w/v and a glycerol concentration of 1% w/v were used for all of the tested proportions. The transparency of the films increased as a function of the addition of MS. Moreover, CF‐based films presented a low solubility and a satisfactory water vapor barrier and showed UV‐radiation‐shielding properties. The presence of MS in the composite film elevated the molecular interactions and led to a more compact structure; this resulted in improved strength, although the elongation still remained low. CF‐based films are a promising material for the formulation of edible films with adequate physicochemical and mechanical properties and high nutritional quality. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42455.